-3c+4=c+96

Simple and best practice solution for -3c+4=c+96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3c+4=c+96 equation:


Simplifying
-3c + 4 = c + 96

Reorder the terms:
4 + -3c = c + 96

Reorder the terms:
4 + -3c = 96 + c

Solving
4 + -3c = 96 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
4 + -3c + -1c = 96 + c + -1c

Combine like terms: -3c + -1c = -4c
4 + -4c = 96 + c + -1c

Combine like terms: c + -1c = 0
4 + -4c = 96 + 0
4 + -4c = 96

Add '-4' to each side of the equation.
4 + -4 + -4c = 96 + -4

Combine like terms: 4 + -4 = 0
0 + -4c = 96 + -4
-4c = 96 + -4

Combine like terms: 96 + -4 = 92
-4c = 92

Divide each side by '-4'.
c = -23

Simplifying
c = -23

See similar equations:

| (24ab)(3)= | | a-17.72=1.6a+4 | | 5x-2c+1=15 | | 24overx=-10 | | -8x^3+5x^2-20x+250=0 | | -8q+8=q+311.3 | | 7.2=-3h | | -7-2x=-25 | | b+179.68=-3.7b+8.6 | | w+137=-2w+8 | | -p+8=p+44 | | 17=5k-02 | | 6.2y+7=2x-8.1 | | y+35.8=-y+5.8 | | x^2-1=15 | | 80-68= | | -29p-68=p+1432 | | 7ks-5=-19 | | 2(5x+4)=3(6x+2) | | 17x-8-13x=2(2x-5)+2 | | 19x+6=-881.3 | | 3x^2+5x-95=0 | | x-(-3)=25 | | 36-(4x+10)=4(x+2)+x | | c+42=-2c-27 | | 3g+5=89 | | 14-9x=-80-8x | | 160=10x-80 | | -13=-377 | | 4e^3X+6=8 | | 5y=30x+15 | | e-885=-21e-5 |

Equations solver categories